Representations, Practices and Senses in the Colombian Literature of the 20th Century - Pulga Infante, Cristian Fabián (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2019)
This writing aims to describe the main statements that gravitated at the moment of analyzing the content of several literary works that described events of the 20th century in Colombia. This in order to recognize the representations, practices and senses of the society throughout the century. The article is orientated largely to answer to the possibility to put in common dialog the study of the historiographical current and its relationship with the literature.